Strategy and Implementation of Effective Sharia Financial Management: Case Study of Muslimeen Suksa School Thailand - Nurhidayati Husna; Rahmayati Yati; Bulkini Sasu (International Conference on Islamic Economic (ICIE), 2026)
This study is motivated by the financial management challenges faced by Islamic educational institutions, including limited budgets, administrative constraints, and the necessity to implement Sharia principles in every financial transaction. The research problem focuses on how the strategies and implementation of Sharia-based financial management are carried out at Muslimeen Suksa School Thailand. This study employs a qualitative method with a descriptive approach to obtain an in-depth understanding of school financial management practices based on Sharia principles. Data were collected through observation, in-depth interviews with the principal, treasurer, and administrative staff, as well as documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, with triangulation of sources, methods, and theories to ensure data validity. The findings indicate that financial management strategies are implemented through participatory budget planning, diversification of funding sources, separation of operational and social funds, and transparent financial reporting. The implementation of Sharia principles is reflected in the avoidance of interest-based transactions and the use of Sharia-compliant contracts in cooperation and procurement activities. The study concludes that Sharia-based financial management at Muslimeen Suksa School has been effectively implemented and is able to strengthen transparency, accountability, and institutional sustainability.